2013
DOI: 10.1016/j.vetpar.2012.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of eprinomectin extended-release injection against induced infections of developing (fourth-stage larvae) and adult nematode parasites of cattle

Abstract: The therapeutic efficacy of eprinomectin in an extended-release injection (ERI) formulation was evaluated against induced infections of developing fourth-stage larval or adult gastrointestinal and pulmonary nematodes of cattle in a series of six studies under two identical protocols (three each for developing fourth-stage larvae or adults) conducted in the USA, Germany or the UK (two studies at each location, one per stage). Each study initially included 16 nematode-free cattle. The cattle were of various bree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 24 publications
1
0
0
1
Order By: Relevance
“…Our results also were partially agreed with Hengge et al (2006) and Kumar and Shekhar (2010) in India who reported that using of Ivermectin resulted in complete resolution of mange crusts and scabs These results displayed in our study were partially agreed with Pourhasan et al (2013) in Ethiopia, who found that the permethrin had the ability to kill mites and its eggs, however, the combination of permethrin with other acaricides was imported to overcome drug resistance development. Our results also were consistent with Rehbein et al (2013) in Ethiopia, who mentioned that injections of ivermectin were highly effective against mites. Nevertheless, Our findings were in approximated with Desoky (2015) in Egypt, who concluded that ivermectin injection was considered the best method to control scabies in animals.…”
Section: Disucssionsupporting
confidence: 92%
“…Our results also were partially agreed with Hengge et al (2006) and Kumar and Shekhar (2010) in India who reported that using of Ivermectin resulted in complete resolution of mange crusts and scabs These results displayed in our study were partially agreed with Pourhasan et al (2013) in Ethiopia, who found that the permethrin had the ability to kill mites and its eggs, however, the combination of permethrin with other acaricides was imported to overcome drug resistance development. Our results also were consistent with Rehbein et al (2013) in Ethiopia, who mentioned that injections of ivermectin were highly effective against mites. Nevertheless, Our findings were in approximated with Desoky (2015) in Egypt, who concluded that ivermectin injection was considered the best method to control scabies in animals.…”
Section: Disucssionsupporting
confidence: 92%
“…) та легень (Dictyocaulus viviparus) жуйних тварин. Також ЕП згубно діє на паразитних членистоногих -паразитиформних і акариформних кліщів, постійних ектопаразитів (волосоїдів, вошей), різних видів мух та гнусу [3].…”
Section: паразитарні хворобиunclassified